2016
DOI: 10.1155/2016/8654169
|View full text |Cite
|
Sign up to set email alerts
|

Current Psychopathological Symptoms in Children and Adolescents Who Suffered Different Forms of Maltreatment

Abstract: The aim of the present study is to evaluate the current psychopathological problems of different forms associated with maltreatment on children's and adolescents' mental health. Ninety-five females and ninety males with a mean age of 8.8 years who have suffered in the last six months different forms of abuse (physical, sexual, and emotional) and neglect were included in the study. The current reaction to trauma as directly observed by clinical instruments was examined. Differences in gender, age at the time of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
1
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 61 publications
1
1
0
2
Order By: Relevance
“…In agreement with previous studies [ 28 , 48 , 49 ], our findings confirmed the non-specific influence of early life adversity across all symptom domains in men and women. Nonetheless, several observations should be noted.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…In agreement with previous studies [ 28 , 48 , 49 ], our findings confirmed the non-specific influence of early life adversity across all symptom domains in men and women. Nonetheless, several observations should be noted.…”
Section: Discussionsupporting
confidence: 93%
“…Furthermore, the findings converged with the follow-up analyses on psychopathology subdomains, showing significant associations of physical and emotional neglect with certain symptom domains among men, but null associations in women. Although some previous studies do not show such gender-specific pattern [ 31 , 49 ], several studies support the idea that neglect domains are more relevant for the pathoetiology of mental health in men. A longitudinal study in Danish offspring of mothers of individuals with schizophrenia showed that institutionalization, which is linked to parental absence, increased symptoms of thought disorder specifically among men [ 60 ].…”
Section: Discussionmentioning
confidence: 88%
“…Los factores que desencadenan la conducta de maltrato infantil son entre otros, la baja situación económica, el desempleo, el hacinamiento y la disfuncionalidad familiar (Pérez y Reinoza, 2011;Cuba, Jurado, Romero y Cuba, 2013;Pérez, 2013;Gómez, et al, 2015). Asimismo, el maltrato infantil antes de los 8 años se relaciona de manera significativa con síntomas somáticos, depresión, ansiedad, aislamiento, alteraciones conductuales como ruptura de normas, conducta agresiva (Fernández-Daza y Fernández-Parra, 2013;De Rose, et al, 2016; Hewitt-Ramírez y Moreno-Méndez, 2018) y conducta antisocial en la adolescencia (Morillo y Birkbeck, 2017).…”
Section: Algunos Aspectos Teóricosunclassified
“…Dies gilt nicht nur für Studien an Erwachsenen, auch bei Kindern und Jugendlichen, die einen Missbrauchs-oder Misshandlungs-bzw. Vernachlässigungserleben innerhalb der letzten sechs Monate berichteten, konnte bei 95,1% irgendeine Form einer psychischen Erkrankung nachgewiesen werden (10). Einen der umfangreichsten systematischen Reviews und eine Metaanalyse zu der Thematik von Gesundheitsfolgen von Kindesmisshandlung und -missbrauch sowie Vernachlässigung wurde von Norman et al (29) Bezogen auf psychische Misshandlungen konnten in Studien anhand von Daten des National Epidemiological Survey on Alcohol and related Conditions aus den Jahren 2004 und 2005 (n = 34 653) der Zusammenhang zwischen Vernachlässigung und psychischer Misshandlung und Folgeerkrankungen geschildert werden.…”
Section: Konsequenzen Für Die Psychische Gesundheitunclassified